Input subsidy withdrawal in India: output loss, cash transfer, and redistribution - Seema Bathla; Anjani Kumar; Roopali Aggarwal (Agricultural Economics Research Review, 2023)
Public expenditure on subsidies for agricultural inputs in India have intensified input consumption and raised the agriculture growth rate. But it exceeds the combined expenditure on capital formation in agriculture and irrigation and is fiscally unsustainable for the exchequer. Input subsidies must be made more effective while sustaining production and farmer income. We estimate the impact on agricultural output if fertilizer and power subsidies are withdrawn. We also consider the resultant increase in their respective prices, the amount to be credited to farmers’ bank accounts under the ambit of the Direct Benefit Transfer programme, and other key implications.